DEVELOPMENT OF A POWER QUALITY MONITORING SYSTEM FOR THREE-PHASE INDUCTION MOTORS USING LABVIEW - Akhyar Muchtar; Dessy Ana Laila Sari; Hilda Ashari; Muhammad Iswal Burhan; Andi Fitriati; Nur Azhari Iriawan (Jurusan Pendidikan Teknik Elektro, 2025)
Three-phase induction motors are widely used in industrial applications. The performance of these motors heavily depends on the stability of electrical parameters such as voltage, current, frequency, and power factor. Imbalances or fluctuations in these parameters can significantly affect the motor’s operational lifespan and may even lead to equipment failure. Therefore, periodic monitoring of these parameters is essential. This study aims to design and develop an electrical power monitoring system for a three-phase induction motor using LabVIEW, integrated with the Modbus RTU protocol and a power meter. Methode of this research is an experimental method. The result of this research is that the current will fluctuate along with the increase in motor load. When unloaded, the current was measured at 0 A. Upon applying one load, the R/S/T phase currents increased to 0.1107 A, 0.1173 A, and 0.1107 A, respectively. With two loads, the currents rose to 0.1357 A, 0.1424 A, and 0.1317 A. When the load increased to three, the R/S/T phase currents further increased to 0.1581 A, 0.1654 A, and 0.1526 A, respectively. Voltage and frequency were observed to remain stable at approximately 238 V and 50 Hz. Inter-phase voltage also remained relatively stable, ranging from 408 V to 413 V. This study is practically aimed at providing an accurate, validated, and real-time monitoring system for three-phase induction motors, which is highly relevant for predictive maintenance in industrial environments. Compared to previous works that relied on low-cost sensors or microcontroller-based monitoring, this research emphasizes higher measurement accuracy, validated results, and seamless integration with industrial communication protocols. In summary, the developed system successfully demonstrated its ability to monitor electrical parameters of three-phase induction motors in real-time with high accuracy, validated measurement results, and stable performance across different load conditions. Its practical contribution lies in offering an industrially applicable monitoring solution that supports predictive maintenance, reduces downtime, and extends motor lifespan. The main scientific contribution of this work is the integration of LabVIEW and Modbus RTU with a validated measurement scheme, overcoming the accuracy and reliability limitations of previous studies.